Effects regularly exercising in two different PM2.5 concentration - Samsul Bahri; Dadan Resmana; Imam Safei (Journal Sport Area, 2022)
Performing exercise or physical activities for a long duration under the exposure of air pollution becomes an unhealthy combination and will increase the risks of the individual inhaling more pollutant. Studies that examine an individual performing physical activities regularly in two public sport centers with different levels of air pollution have not been extensively documented, therefore the purpose of this study is to evaluate effects of regular exercise on aerobic capacity, force vital capacity (FVC), and hematological profile among individuals in an environment with similar climatic characteristics but different concentrations of air pollution. This trial composed 15 males (age range from 16 to 18) from Bandung City, Indonesia. Two public sport centers with similar climatic conditions (temperature, and humidity), but different concentrations of air pollutants are selected. Participants performed exercises three times a week for three consecutive weeks at each research site, with a two-week break. Participants’ aerobic capacity, respiratory capacity, and blood sample are measured before and after they exercised at each site. The measured parameters in both sites are compared and analyzed. Aerobic capacity, FVC, and RBC after participants exrcised in the area with lower air pollution show higher value than exercised in the area with higher air pollution. Manwhile WBC is shown to be high after participants exercised in the area with higher air pollution. This happened because air pollution has effect to human physiological characteristics. This research shows that exercising at sport center with high air pollution had negative effect on hematology profile and could affect the development of aerobic and respiratory capacities. The limitations in this study are the unknown intensity when doing regular physical exercise so that in future studies it is recommended to determine whether the intensity will affect the variables in the research subject.